Polycyclic Aromatic Hydrocarbons (PAHs) in Grilled Marshmallows - Maciej Maciejczyk; Beata Janoszka; Magdalena Szumska; Beata Pastuszka; Sławomir Waligóra; Aleksandra Damasiewicz-Bodzek; Agnieszka Nowak; Krystyna Tyrpień-Golder (Molecules, 2024)
The aim of this study was to assess potential health risks among children and adolescents consuming various grilled marshmallows using a survey and to determine polycyclic aromatic hydrocarbons (PAHs) in these food products. PAH analysis in grilled marshmallows included a dilution stage with deionized water and liquid–liquid extraction with cyclohexane and solid-phase extraction (SPE). PAH fractions were initially analyzed via high-performance thin-layer chromatography, and PAH concentrations were determined via gas chromatography with a tandem mass detector using the selective reaction monitoring (SRM) mode. This study on the consumption of grilled marshmallows was conducted among approximately 300 children and adolescents. The preliminary results indicated that “raw” marshmallows did not contain PAHs. However, the obtained data suggested the exposure of young people to carcinogenic PAHs from grilled marshmallows (63.5% of them consumed marshmallows). Carcinogenic benzo(a)pyrene (BaP) was determined in all samples. The profile of PAH concentrations in the extracts isolated from various grilled types of marshmallows was similar (r2 > 0.8000), regardless of the grilling method. Compared to the white sugar confection, higher concentrations of PAHs were determined in multicolored marshmallows. The lack of social awareness about exposure to carcinogenic substances is alarming.